KONSUMSI RUMPUT LAUT DAPAT MENGATASI ANEMIA KEHAMILAN: Consumption of Seaweed Can Overcome Anemia in Pregnancy - Melly Damayanti; Astri Yulia Sari Lubis; Wahyu Eny Setyohari (LPPM - STIKES Pemkab Jombang, 2020)
Anemia in pregnancy is a condition in pregnant women with hemoglobin levels less than 11gr% during pregnancy. An increased of anemia often occurs in the third trimester of pregnancy. Pregnant women needs to be supported with nutritional patterns which contain some necessary intermediate in the synthesis of hemoglobin, which is seaweed. Seaweed type Euchoma sp contains iron, a mixture of which is needed in the synthesis of hemoglobin, has a high bioavailability of substances and is able to stabilize the number of red blood cells, white blood cells, and hemoglobin. The purpose of the study was to determine the status of anemia before and after the study. The study design is the pre-post test design. The population of the study was 30 third trimester pregnant women in the Tanjung Pinang City Primary Health Care Work Area. Respondents were given seaweed as much as 200 gram for 7 days and the 8th day repeated hemoglobin levels were measured. After being given an intervention, there was an increase in hemoglobin levels in pregnant women by 1.2gr% and there were no more respondents suffering anemia. Keywords : consumption of seaweed, anemia in pregnancy